The law and practice of international administrative tribunals / Asier Garrido Muñoz, Jason Morgan-Foster, Daniel Peat, Anne-Marie Thévenot-Werner. - Garrido Muñoz, Asier; Morgan-Foster, Jason; Peat, Daniel; Thévenot-Werner, Anne-Marie (Cambridge University Press, 2026)
The jurisprudence of international administrative tribunals holds great relevance for international organisations, as seen in the proliferation of these tribunals, the complexity of their jurisprudence, and their practical impact. This book provides a comprehensive and accessible analysis of essential topics in this field, including applicable sources, jurisdiction and admissibility, grounds for review, equality and non-discrimination, and remedies. It also covers key emerging issues, such as the rights of non-staff personnel, the growing application of international human rights law by tribunals, and the protection of acquired rights. Drawing on thousands of decisions, this book is an invaluable resource for both practitioners and scholars. For practitioners, it offers a practical guide to navigating complex cases. For scholars, it highlights common principles and key divergences across the jurisprudence of some thirty tribunals, at the same time illuminating the increasingly sophisticated interplay between international administrative law and public international law.